2008
DOI: 10.1080/02688690802354210
|View full text |Cite
|
Sign up to set email alerts
|

Does conservative management for brain stem cavernomas have better long-term outcome?

Abstract: There has been a controversy in the last 15 years on the correct management of brain stem cavernomas. We have reviewed our experience of the last 10 years in a single Institution and reviewed related literature published in the last 15 years. We recorded the demographics, clinical presentation, rebleeding episodes, incidence of neurological events and outcome assessed by recording the change of the modified Rankin scale in 21 cases. Univariate analysis was applied to test the effect of demographics, and presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…20 The percentage of improved or unchanged functional outcomes was retrospectively reported in relatively small cohorts and ranged from 46.7% to 95.7%. 10,16,23 This study demonstrated that an initial small lesion size, no prospective hemorrhage, and younger age contributed to promote complete recovery. These findings were interpreted as implying that a significant space-occupying effect, cumulative impairment caused by repeated hemorrhages, and advanced age with decreasing potential of rehabilitation or functional compensation would delay or even inhibit functional improvement.…”
Section: Functional Outcomesmentioning
confidence: 59%
“…20 The percentage of improved or unchanged functional outcomes was retrospectively reported in relatively small cohorts and ranged from 46.7% to 95.7%. 10,16,23 This study demonstrated that an initial small lesion size, no prospective hemorrhage, and younger age contributed to promote complete recovery. These findings were interpreted as implying that a significant space-occupying effect, cumulative impairment caused by repeated hemorrhages, and advanced age with decreasing potential of rehabilitation or functional compensation would delay or even inhibit functional improvement.…”
Section: Functional Outcomesmentioning
confidence: 59%
“…In studies on the natural history of CMs (Table 9), the documented subdivided annual hemorrhage rates for brainstem CMs differed greatly and were noted to be 2.33% if retrospective 13 annual hemorrhage rate of 2.46%, a clinical event rate of 3.4%, and a rehemorrhage rate of 5.1%. Another study by Tarnaris et al 47 retrospectively cited a similar rehemorrhage rate of 5% in 21 cases of conservatively managed brainstem CMs. These diversities could be ascribed, as previously stated, to the limited number of patients, an insufficient followup duration, and the variance in individual study design.…”
Section: Hemorrhage Riskmentioning
confidence: 85%
“…10,11,14,19,22,30,34,37,38,42,47,51 Among these studies, Tarnaris et al 47 reported fairly poor outcomes, with 53.3% of patients exhibiting worsening conditions, and cited a neurological deterioration of 10% per patient year. An extremely malignant prognosis was reported with a mortality rate of 20%.…”
Section: Functional Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…13.5 mm 24.3 mm p 0.0001 p 0.9375 Fig. 3 undesirable events p 0.0040 21 Wang CW et al 25 Gross BA et al 8 Abla AA et al …”
mentioning
confidence: 96%